A new algorithm for construction of coarse‐grained sites of large biomolecules. Issue 9 (15th December 2015) - Li, Min; Zhang, John Z. H.; Xia, Fei
Abstract : The development of coarse‐grained (CG) models for large biomolecules remains a challenge in multiscale simulations, including a rigorous definition of CG representations for them. In this work, we proposed a new stepwise optimization imposed with the boundary‐constraint (SOBC) algorithm to construct the CG sites of large biomolecules, based on the s cheme of essential dynamics CG. By means of SOBC, we can rigorously derive the CG representations of biomolecules with less computational cost. The SOBC is particularly efficient for the CG definition of large systems with thousands of residues. The resulted CG sites can be parameterized as a CG model using the normal mode analysis based fluctuation matching method. Through normal mode analysis, the obtained modes of CG model can accurately reflect the functionally related slow motions of biomolecules. The SOBC algorithm can be used for the construction of CG sites of large biomolecules such as F‐actin and for the study of mechanical properties of biomaterials. © 2015 Wiley Periodicals, Inc. Abstract : The multiscale simulation of biomolecules requires a rigorous definition of their coarse‐grained (CG) representation. A stepwise optimization imposed with the boundary‐constraint (SOBC) algorithm is developed to construct the CG sties of large biomolecules. The graph shows a four‐site CG model of G‐actin monomer derived from SOBC.